Desenvolvimento de raízes de cenoura (Daucus carota l. var. Esplanada) em solo submetido a diferentes compostos orgânicos - Martins, Gustavo de Oliveira (2008)
The mini-carrot commerce is increasing, in Brazil, alongside of the years. An exigent market presuppose high-quality products and in sufficient amount to attend it. So, organic fertilization shows itself like a very important instrument to obtain more healthy products and to maintenance a no expensive sustainable production. Thus, this work searched evaluate the development of carrot Esplanada roots, cultivated using different organic compounds. The treatments consisted in the application of 12 compounds, bovine manure and mineral fertilizer, on a Podzol hydromorphic eutrophic from Arapiraca-AL, being the plants of carrot cultivated in a greenhouse resulting in 14 treatments. These treatments were put in a completely randomized blocks design using four replications. Were evaluated: length, diameter, roots production and nitrogen, phosphorus, potassium, calcium and magnesium content. The organic compounds were made up from two basic mixes: MBsugarcane (mix with sugarcane bagasse + sugar plant filter cake + bovine manure + natural phosphate) and MBcoconut (mix where the sugarcane bagasse was changed by coconut bagasse) using increasing stillage doses, obtaining different compounds: C1: MBsugarcane; C2: MBsugarcane + 25% stillage solution; C3: MBsugarcane + 50% stillage solution; C4: MBsugarcane + 75% stillage solution; C5: MBsugarcane + 100 % stillage; C6: MBsugarcane + water + potassium sulfate; C7: MBcoconut; C8: MBcoconut + 25% stillage solution; C9: MBcoconut + 50% stillage solution; C10: MBcoconut + 75% stillage solution; C11: MBcoconut + 100 % stillage and C12: MBcoconut + water + potassium sulfate. The data had been submitted to the analysis of variance and the averages compared between itself for the Tukey test, with P < 0,05, besides of the orthogonal contrast for phosphorus content of the roots. Statistical differences were not found between the treatments to the length, diameter and roots production variables. In relation to the nutrients absorption, there were not statistical difference, except to the phosphorus absorption, with the compounds made up of sugarcane bagasse, showing a better result than the others treatments.